Automatic parameterization of a flow routing scheme driven by radar altimetry data: Evaluation in the Amazon basin. Issue 1 (30th January 2013) - Getirana, Augusto C. V.; Boone, Aaron; Yamazaki, Dai; Mognard, Nelly
Key Points calibration of a flow routing scheme with radar altimetry data sensitivity of the calibration to data availability reliability of parameters found